2017
DOI: 10.18632/oncotarget.23170
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and novel thioglycosides exert suppressive effect on human breast and colon carcinoma cells

Abstract: The rationale for the implementation of novel therapies should be based on hallmarks of cancer. Two novel compounds labelled as thioglycoside A and B were designed and evaluated on breast and colon cancer cell lines. We assessed their cytotoxic effect after sensitizing cancer cells with insulin. In order to explore the underlying mechanisms, we performed tests to assess cell migration and motility, apoptosis, expression of glucose transporter 1 and proapoptotic proteins. Both compounds proved to have an antitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We and others have designed new syntheses for pyridine thioglycosides, which have shown strong cytotoxicity against various human cancer cell lines and block proliferation of various cancer cell lines (Komor et al, 2012;Elgemeie et al, 2015). It has also been shown that thioglycosides involving pyridine and dihydropyridine groups exert inhibitory effects on both DNA-containing viruses and inhibitors of protein glycosylation (Agrawal et al, 2017;Elgemeie et al, 2010;Masoud et al, 2017). Based on these significant biological findings and with the aim of identifying new potent chemotherapeutics as new anticancer agents with improved pharmacological and safety profiles, we have prepared several new non-classical thioglycosides containing the pyridine ring.…”
Section: Chemical Contextmentioning
confidence: 99%
“…We and others have designed new syntheses for pyridine thioglycosides, which have shown strong cytotoxicity against various human cancer cell lines and block proliferation of various cancer cell lines (Komor et al, 2012;Elgemeie et al, 2015). It has also been shown that thioglycosides involving pyridine and dihydropyridine groups exert inhibitory effects on both DNA-containing viruses and inhibitors of protein glycosylation (Agrawal et al, 2017;Elgemeie et al, 2010;Masoud et al, 2017). Based on these significant biological findings and with the aim of identifying new potent chemotherapeutics as new anticancer agents with improved pharmacological and safety profiles, we have prepared several new non-classical thioglycosides containing the pyridine ring.…”
Section: Chemical Contextmentioning
confidence: 99%
“…The elevated glucose intake requires the overexpression of glucose transporters (GLUTs), which is frequent in neo-plasms and provide clinical targets for therapy [ 7 , 8 ]. Therefore, glycoconjugation, in which cytotoxic agents or targeted anticancer therapeutics have been linked to glucose, can improve the selective uptake of anticancer drugs [ 9 , 10 , 11 , 12 , 13 , 14 ]. Since the introduction of glufosfamide [ 15 ], the potential of this strategy in diagnosis and therapy has already been realized, yet there is tremendous scope for improvement [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, insulin enhances cisplatin-induced apoptosis in human esophageal squamous cell carcinoma EC9706 cells [ 17 ]. Insulin enhances the effects of chemotherapeutic agents on colorectal cancer while single using not showing toxicity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%